Screening and Characterization of Thermostable Amylase-Producing Bacteria Isolated from Soil Samples of Afdera, Afar Region, and Molecular Detection of Amylase-Coding Gene. (10th May 2021) - Yassin, Semira Nureddin; Jiru, Tamene Milkessa; Indracanti, Meera
Abstract : Studying thermostable amylase-producing bacteria in extreme environments has a crucial role to overcome different industrial challenges. Afar Region is one of the hottest and salty areas, making it the home of extremophiles. This study aimed at screening and characterizing amylase-producing bacteria isolated from soil samples of Afdera, Afar Region, and detection of their amylase-coding genes. Thus, a total of 49 bacterial isolates were obtained from the collected soil samples. Out of these, three isolates (M2, M8, and M13) were selected on the basis of diameter of the average clear zone formation and time taken to decolorize iodine solution. Based on their morphological and biochemical characteristics, the isolates were identified as genus Bacillus . PCR amplification and detection of the amylase-coding gene confirmed the presence of the amylase gene in the three bacterial isolates. Optimum amylase production time for these isolates was 48 hrs (M13 and M8) and 72 hrs (M2) corresponding to the amylase activity of 0.67 U/mL for M13, 0.74 U/mL for M8, and 0.73 U/mL for M2 with an optimum temperature of 55°C. Studies on the effect of temperature revealed that the crude enzyme had a maximum activity and stability at 75°C, 70°C, and 65°C for isolates M13, M8, and M2, respectively. Additionally, amylase produced from all isolates retained more than 66.41% of their original activity after incubating them at a temperature range from 55 to 80°C for 50 min. Optimum pH for the activity of all crude amylases was in the range from 5 to 9 with a peak activity at pH 8. Their activity decreased significantly by the presence of Zn +2 and Mg 2+ ; however, their activity increased by the presence of Ca +2 . Moreover, the three crude amylases were stable (0–3 M) with NaCl concentration. Amylases of this finding with thermophilic and halophilic characteristics offer a wide range of applications in food, brewing, textile, starch, paper, and deterrent industries. Thus, identification of these Bacillus isolates at a molecular level and purification as well as detailed characterization of the types of amylases are recommended for effective utilization in different industries.